Sharing for Health, Inclusion, and Sustainability: The Co-Production of Outdoor Equipment Lending in Norway - Eigil Barratt-Due Solum, Espen; Førde, Anniken; Guillen-Royo, Monica (Urban Planning, 2024)
This study analyses the promotion of public health, social inclusion, and environmental sustainability in two Norwegian cities through the co-production of outdoor equipment-lending outlets. Building on seminal insights from Elinor Ostrom, we investigate how the co-production of equipment-lending initiatives can bridge the divide between government, civil society, and the market. Engaging citizens in outdoor activities to promote public health, social inclusion and sustainability is a political focus area in Norway, but the activities often demand access to expensive equipment. Since the 1990s, many Norwegian municipalities have organised lending outlets for outdoor equipment, often relying on volunteer work. The emergence of BUA, a nationwide NGO aimed at engaging children and youth in outdoor activities, added the goal of environmental sustainability as a foundation for equipment-lending outlets. Additionally, it became a catalyst for the articulation of a diverse array of partnerships for the co-production of equipment lending as a public service. This study draws on fieldwork and in-depth interviews with users, staff, volunteers, and institutional partners at two lending outlets, in Kolbotn and Tromsø, in south-eastern and northern Norway. We focus on the co-production of BUA as a public service and discuss how the interplay of various actors leads to the achievement of societal and environmental goals, and subsequently how equipment-lending initiatives can facilitate collaborative consumption practices with the potential to reduce consumption.